2022
DOI: 10.3389/fcvm.2022.849032
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Diagnosis and Functional Assessment of Coronary Artery Disease in Patients With Severe Aortic Stenosis

Abstract: More than half of patients with severe aortic stenosis (AS) over 70 years old have coronary artery disease (CAD). Exertional angina is often present in AS-patients, even in the absence of significant CAD, as a result of oxygen supply/demand mismatch and exercise-induced myocardial ischemia. Moreover, persistent myocardial ischemia leads to extensive myocardial fibrosis and subsequent coronary microvascular dysfunction (CMD) which is defined as reduced coronary vasodilatory capacity below ischemic threshold. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 125 publications
(397 reference statements)
1
6
0
3
Order By: Relevance
“…Furthermore, the vasodilatory capacity of coronary arterioles in patients with increased LVEDP, in our case being related to persisting, large myocardial ischemia and LV dysfunction, is reduced or exhausted at rest; thus, the vasodilatory effect of adenosine on microcirculatory resistance is limited. A similar condition has been described in patients with severe aortic stenosis, where LVEDP reduction by transcatheter aortic valve replacement leads to immediate recovery of coronary microcirculatory resistance and increased hyperemic flow velocity 4 . In our patient, LV unloading and LVEDP decreasing by Impella, coupled with the device‐related increase of aortic pressures and reduction of coronary pressures, restored the coronary autoregulation pathways, in particular improving the physiological diastolic “suction wave” and increasing coronary flow.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the vasodilatory capacity of coronary arterioles in patients with increased LVEDP, in our case being related to persisting, large myocardial ischemia and LV dysfunction, is reduced or exhausted at rest; thus, the vasodilatory effect of adenosine on microcirculatory resistance is limited. A similar condition has been described in patients with severe aortic stenosis, where LVEDP reduction by transcatheter aortic valve replacement leads to immediate recovery of coronary microcirculatory resistance and increased hyperemic flow velocity 4 . In our patient, LV unloading and LVEDP decreasing by Impella, coupled with the device‐related increase of aortic pressures and reduction of coronary pressures, restored the coronary autoregulation pathways, in particular improving the physiological diastolic “suction wave” and increasing coronary flow.…”
Section: Discussionsupporting
confidence: 82%
“…A similar condition has been described in patients with aortic stenosis, where LVEDP reduction by transcatheter aortic valve replacement leads to immediate recovery of coronary microcirculatory resistance and increased hyperemic flow velocity. 4 In our patient, LV unloading and LVEDP decreasing by Impella, coupled with the device-related increase of aortic pressures and reduction of coronary pressures, restored the coronary autoregulation pathways, in particular improving the physiological diastolic "suction wave" and increasing coronary flow. This "unmasked" the functional severity of LM stenosis.…”
Section: Case Descriptionmentioning
confidence: 54%
“…In addition, diastolic filling time and the severity of the aortic valve area have been positively correlated to reduced CFR [ 34 ]. Thus, even in the absence of epicardial CAD, ischemia can occur, further triggering fibrotic changes in the myocardium and inducing angina [ 35 ]. Due to these factors, the presence of angina has a low positive predictive value for CAD in patients with aortic stenosis [ 2 ].…”
Section: Functional Assessment Of the Coronary Arteries—basic Princip...mentioning
confidence: 99%
“…From a pathophysiological perspective, because LV hypertrophy leads to external compression of the microvasculature and relative capillary rarefication, the resting vasodilatory capacity to maintain stable coronary flow is already exhausted in AS patients [ 38 , 47 ]. Thus, the vasodilatory response to adenosine is attenuated during FFR measurement, which may lead to false negative (too high) FFR values in intermediate epicardial stenoses and subsequent underestimation of stenosis severity [ 35 ]. Structural and functional alterations of the microvasculature further contribute to this finding, including perivascular fibrosis, arteriolar remodeling, endothelial dysfunction, and a higher sympathetic tone, all of which lead to a higher hyperemic microvascular resistance with subsequent attenuation of the vasodilatory effect of adenosine [ 34 , 38 , 47 , 48 ].…”
Section: Functional Assessment Of the Coronary Arteries—basic Princip...mentioning
confidence: 99%
“…The FFR is measured over the entire cardiac cycle during maximal hyperaemia using adenosine and is expressed as the ratio of the mean coronary pressure distal to stenosis relative to the mean proximal aortic pressure. Adenosine is a potent vasodilator of coronary arterioles and can be safe, but has also been associated with haemodynamic instability in the presence of severe AS with coexisting CAD 27. Some small observational studies have suggested that percutaneous coronary intervention (PCI) under FFR guidance in TAVI recipients with CAD may lead to improved clinical outcomes in comparison with angiography-guided PCI, but this is yet to be established in a randomised controlled trial (RCT) 28…”
Section: Invasive Functional Evaluation Of Coronary Artery Stenosis S...mentioning
confidence: 99%